A taxonomic revision of the genus Baldorhynchus (Di Marco & Osella, 2002) stat. n. (Coleoptera, Curculionidae, Entiminae) - Bello, Cesare; Osella, Giuseppe; Baviera, Cosimo (Zootaxa, 2016)
The Otiorhynchus subgenus Baldorhynchus Di Marco & Osella, 2002 is revised and elevated to the genus level, stat. n.. The following species-level taxa were also elevated to the species level: Baldorhynchus caoduroi (Osella, 1983) stat. n. from Otiorhynchus (Baldorhynchus) amicalis caoduroi (Osella, 1983); Baldorhynchus comottii (Osella, 1983) stat. n. from Otiorhynchus (Baldorhynchus) moczarskii comottii (Osella, 1983); Baldorhynchus lessinicus (Osella, 1983) stat. n. from Otiorhynchus (Baldorhynchus) amicalis cenomanus (Colonnelli & Magnano, 2003) = Troglorhynchus amicalis ssp. lessinicus (Osella, 1983); Baldorhynchus toscolanus (Osella, 1983) stat. n. from Otiorhynchus (Baldorhynchus) kahleni toscolanus (Osella, 1983) and Baldorhynchus valvestinus (Osella, 1983) stat. n. from Otiorhynchus (Baldorhynchus) kahleni valvestinus (Osella, 1983). The following new combinations and resurrections are also proposed: Baldorhynchus carinatus (Osella, 1983) nom. res. from Troglorhynchus carinatus Osella (1983) = Otiorhynchus (Troglorhynchus) serradae Colonnelli & Magnano (2003); Otiorhynchus (Troglorhynchus) radjai (Di Marco & Osella, 2002) comb. n. from Otiorhynchus (Baldorhynchus) radjai Di Marco & Osella (2002); Baldorhynchus ferrarii (F.Solari, 1955) nom. res. from Troglorhynchus ferrarii F. Solari (1955) = Otiorhynchus (Baldorhynchus) adrianoi Magnano (2001); Baldorhynchus judicariensis (Osella, 1983) nom. res. from Troglorhynchus judicariensis Osella (1983) = Otiorhynchus (Baldorhynchus) clibbianus Colonnelli & Magnano (2003); Baldorhynchus lessinicus (Osella, 1983) nom. res. from Troglorhynchus amicalis ssp. lessinicus Osella (1983) = Otiorhynchus (Baldorhynchus) amicalis cenomanus (Colonnelli & Magnano, 2003). Twenty-one species are new to science: Baldorhynchus agostianus Bellò & Osella sp. n., Baldorhynchus anachoreta Bellò & Osella sp. n., Baldorhynchus bodeianus Bellò & Osella sp. n., Baldorhynchus branchianus Bellò & Osella sp. n., Baldorhynchus cohabitator Bellò & Osella sp. n., Baldorhynchus danzii Bellò & Osella sp. n., Baldorhynchus deceptor Bellò & Osella sp. n., Baldorhynchus grottoloi Bellò & Osella sp. n., Baldorhynchus magasaensis Bellò & Osella sp. n., Baldorhynchus marianus Bellò & Osella sp. n., Baldorhynchus metallarius Bellò & Osella sp. n., Baldorhynchus monguzzii Bellò & Osella sp. n., Baldorhynchus nardii Bellò & Osella sp. n., Baldorhynchus paladinii Bellò & Osella sp. n., Baldorhynchus pedersolii Bellò & Osella sp. n., Baldorhynchus pivai Bellò & Osella sp. n., Baldorhynchus regalini Bellò & Osella sp. n., Baldorhynchus ruzzieri Bellò & Osella sp. n., Baldorhynchus saccoi Bellò & Osella sp. n., Baldorhynchus settei Bellò & Osella sp. n. and Baldorhynchus tedeschii Bellò & Osella sp. n.. Thirty-seven species are assigned to the genus Baldorhynchus. Finally, in addition to having redescribed Baldorhynchus moczarskii (Breit, 1913), we designate a neotype for Baldorhynchus baldensis (Czwalina, 1875). A key to species and groups of species, a checklist of all species, diagnosis, distribution maps and details of ecology are provided.